(untitled) (Revista de Estudos da Linguagem, 2003)
The aim of this paper is to present some of the studies on theacquisition of Brazilian Portuguese as a first language, which havebeen published in the last few years in our country, making use ofthe generative grammar theory in their analysis of the child´s speechdata. The topics that have been analysed are the systems: D, IP, CP,and complementation/adjunction in complex sentences. Additionalresearch on the acquisition of Brazilian Portuguese as a secondlanguage is also shown. The studies briefly discussed here cancontribute to prove the relevance of the generative theory in thedevelopment of the Language Acquisition area.